A polyextremophilic alcohol dehydrogenase from the Atlantis II Deep Red Sea brine pool. Issue 2 (18th December 2018) - Akal, Anastassja L.; Karan, Ram; Hohl, Adrian; Alam, Intikhab; Vogler, Malvina; Grötzinger, Stefan W.; Eppinger, Jörg; Rueping, Magnus
Abstract : Enzymes originating from hostile environments offer exceptional stability under industrial conditions and are therefore highly in demand. Using single‐cell genome data, we identified the alcohol dehydrogenase (ADH) gene, adh/a1a, from the Atlantis II Deep Red Sea brine pool. ADH/A1a is highly active at elevated temperatures and high salt concentrations (optima at 70 °C and 4 m KCl) and withstands organic solvents. The polyextremophilic ADH/A1a exhibits a broad substrate scope including aliphatic and aromatic alcohols and is able to reduce cinnamyl‐methyl‐ketone and raspberry ketone in the reverse reaction, making it a possible candidate for the production of chiral compounds. Here, we report the affiliation of ADH/A1a to a rare enzyme family of microbial cinnamyl alcohol dehydrogenases and explain unique structural features for halo‐ and thermoadaptation. Abstract : A polyextremophilic alcohol dehydrogenase (ADH) was identified from single amplified genomes of the Atlantis II brine pool and was characterized in terms of activity and stability. The ADH was stable under high temperatures and hypersaline conditions, tolerated organic solvents, and preferably converted cinnamyl alcohol derivatives. Adaptation strategies and phylogenetic relations were investigated and revealed a member of an undiscovered ADH family.